2022
DOI: 10.1002/pits.22722
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in school and cyberbullying among adolescents without and with special educational needs in emotional–social development and in learning in Germany

Abstract: Bullying in school and cyberbullying are highly relevant issues. Students with special educational needs in emotional–social development and learning show individual characteristics that could be risk factors for bullying perpetration and victimization (e.g., externalizing behavior problems or poor social skills). Therefore, the present study was carried out to explore differences in school bullying and cyberbullying between adolescents without and with the aforementioned special educational needs. A cross‐sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Studii anterioare au arătat că în general adolescenții nu prea fac diferență dintre bullying și cyberbullying [22], de asemenea, într-un studiu recent publicat care a evaluat fenomenele de bullying și cyberbullying din Germania s-a determinat că există o asociere pozitivă puternică între aceste două fenomene, deoarece tinerii care au acumulat un scor sporit la bullying în școală au prezentat scoruri sporite și la cyberbullying [6]. Este clar că mediul este cel care face diferența esențială dintre aceste două fenomene, dar și anumite caracteristici definitorii.…”
Section: Journal Of Social Sciencesunclassified
See 2 more Smart Citations
“…Studii anterioare au arătat că în general adolescenții nu prea fac diferență dintre bullying și cyberbullying [22], de asemenea, într-un studiu recent publicat care a evaluat fenomenele de bullying și cyberbullying din Germania s-a determinat că există o asociere pozitivă puternică între aceste două fenomene, deoarece tinerii care au acumulat un scor sporit la bullying în școală au prezentat scoruri sporite și la cyberbullying [6]. Este clar că mediul este cel care face diferența esențială dintre aceste două fenomene, dar și anumite caracteristici definitorii.…”
Section: Journal Of Social Sciencesunclassified
“…Cu toate că inițial cyberbullying era perceput drept o altă formă de bullying, fiind definit ca o agresiune ce are loc în mediul electronic, ulterior s-au conturat alte particularități ale cyberbullying-ului, care îl fac diferit de bullying-ul tradițional. Iată de ce mai mulți cercetători la nivel internațional recomandă realizarea studiilor care să se concentreze exclusiv pe fenomenul de cyberbullying [4,5,6], pentru a putea evalua obiectiv fenomenul, argumentând necesitatea mai multor studii în acest domeniu.…”
unclassified
See 1 more Smart Citation
“…Current research shows that bullying positively influences internalizing and externalizing behavior problems, suicidal thoughts, and psychosomatic complaints and is negatively associated with peer attachment [6,[15][16][17]. Considering the severe effects that bullying can have on both bullies and victims, research focuses on the possible protective and risk factors for bullying [42][43][44]. There is no standardized definition of bullying, but it is generally considered a form of aggressive behavior aimed to intentionally harm a weaker person (physically or psychologically) over an extended period of time.…”
Section: Bullyingmentioning
confidence: 99%
“…In terms of age, the majority of studies have suggested that older students are less likely to experience peer-victimization than younger students [14,15], possibly because older adolescents have greater awareness on how to stop harassment by peers [12]. Other studies have suggested that personal characteristics such as learning disabilities, poor academic performance, poor social skills, and emotional and behavioural problems also increase the likelihood of peer-victimization for adolescents [16][17][18][19]. Research has also suggested that the risk of being bullied is higher among adolescents with minority status, such as racial or ethnic minorities, sexual minority groups and youth with disabilities [20].…”
Section: Introductionmentioning
confidence: 99%